Enhancement of non-specific immune response, resistance and growth of (Litopenaeus vannamei) by oral administration of nucleotide - Manoppo, Henky; Sukenda, .; Djokosetiyanto, Daniel; Sukadi, Mochamad Fatuchri; Harris, Enang (Indonesian Society of Scientific Aquaculture (ISSA), 2011)
This research evaluated the nonspecific immune responsse, resistance, and growth of Litopenaeus vannamei fed nucleotide diet. Shrimp juveniles (mean weight 5.39±0.56 g) were reared in two groups of glass aquaria, each with three replications. Shrimps in group one and group two were fed nucleotide diet and basal diet each for four weeks. Total haemocyte count (THC) and PO activity were evaluated at the end of feeding while growth was measured at two weeks interval. At the end of feeding trial, the shrimps were intramuscularly injected with Vibrio harveyi 0.1x106 cfu.shrimp-1. THC of shrimp fed nucleotide diet significantly increased (P